A New Method of Separating Materials of Different Specific Gravities ? Discussion (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
[This paper was presented for the author, who is now in the National service, by H. M. Chance, and was illustrated by a working model built to the plans shown in the Bulletin, for February, 1918, p. 268. For more convenient operation, a small motor-driven centrifugal pump was attached to the overflow outlet (5, Fig. 1, p. 267) delivering to the inlet, 4. The pressure of ingoing water was then adjusted by a valve at 4, and was indicated by the column of water in a vertical glass tube connecting with the pressure chamber; an average pressure of 15 in. of water column was maintained during the demonstration. The sand used in the test was beach sand, which had simply been passed through a 20-mesh screen; about 45 per cent. was finer than 80 mesh. The circulation of water was at the rate of about 5 gal. per square foot per minute, and the rising velocity of the water in the box as a whole (not the velocity of the jets) was 6 in. per minute. At this consistency, the specific gravity of the fluid mass was between 1.55 and 1.60. Mr. Chance estimated that it would be possible to maintain a fluid mass of this consistency, 3 ft. deep, and with an area of 50 by 60 ft. with an expenditure of 15-hp. Mr. Chance then showed how a lump of coal would float on the fluid mass, and also made a separation of slate from coal on a small scale in a wire cage submerged momentarily in the fluid. The following demonstration relates to a matter not contained in the original paper, and was presented as of interest to the operators of cyanide and other lixiviation processes dealing with fluid mixtures of varying specific gravity.-Ed.]